A NEW PERSPECTIVE ON THE SOCIAL CAUSES AND RESEARCH METHODS IMPACTING PREMATURE BIRTH (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
A lot of methods for studying premature babies are given and analyzes based on modern technologies are considered. The data of research literature in Russian in the cyberleninka.ru, e LIBRARY electronic search engines in the Scopus international databases for the period 2018-2022 were processed and analyzed.